Parametric Optimisation of Plasma Focus Devices for Neutron Production - Lim, L. K.; Yap, S. L.; Lim, L. H.; Neoh, Y. S.; Khan, M. Z.; Ngoi, S. K.; Yap, S. S.; Lee, S. (Springer US, 2015)
A large number of experimental investigations have been carried out on plasma focus devices especially at low energy level of several kJ or over 100 kJ. There are few machines operating in the middle energy range of 10–50 kJ, where the neutron yield typically in the order of 108–109 per shot. This paper reviews the optimisation process of two different plasma focus devices (12 kJ) by applying the Lee model code. The neutron yield (Y n ) versus pressure (P) curve for several configurations of the two plasma focus provided insight of geometrical optimisation. Measured discharge current is fitted as the first step of modelling to correctly simulate the plasma dynamics. Subsequently the code is used to simulate the neutron yield of the two plasma focus devices based on beam target mechanism. Good agreement between the computed results of neutron yield versus pressure and the measured yield versus pressure is found up to the pressure where highest neutron yield is obtained. Computed highest neutron yield for most of the configuration typically differ by a factor <2.